Exchange rates and the information channel of monetary policy - Oliver Holtemöller; Alexander Kriwoluzky; Boreum Kwak (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We disentangle the effects of monetary policy announcements on real economic variables into an interest rate shock component and a central bank information shock component. We identify both components using changes in interest rate futures and in exchange rates around monetary policy announcements. While the volatility of interest rate surprises declines around the Great Recession, the volatility of exchange rate changes increases. Making use of this heteroskedasticity, we estimate that a contractionary interest rate shock appreciates the dollar, increases the excess bond premium, and leads to a decline in prices and output, while a positive information shock appreciates the dollar, decreases prices and the excess bond premium, and increases output.
Keywords: C36; E52; E58; 330; monetary policy; central bank information shock; identification through heteroskedasticity; high-frequency identification; proxy SVAR